AKSES PINTU MENGGUNAKAN KARTU LOBANG TERINTEGRASI BERBASIS MIKROKONTROLER AT89C51 - Ginta, Prama Wira; Sapri, Sapri (Jurnal Media Infotama, 2011)
Door Access Card Integrated Hole Bassed Microcontroller AT89C51 Delphi Programming language as a program to interface to computer and the C language as a program for the microcontroller. In making the program, the authors use a computer with Microsoft Windows XP. The result the program open and close the door by using a microcontroller can be appliedin inproving the cecurity door and the door strongbox . Procedure for immediate access by entering the hole cards, Password and with computer. Monitoring is done trough an interface on a computer screen.Keyword : Hole Cards, Access Doors, Automatic.